2018
DOI: 10.2147/imcrj.s167722
|View full text |Cite
|
Sign up to set email alerts
|

Removal of silicone oil droplets adhering to the posterior surface of an intraocular lens (IOL)

Abstract: PurposeWe report a rare case of silicone oil droplets adhering to the posterior surface of an intraocular lens (IOL) after removal of silicone oil for a patient with retinal reattachment, who had a history of pseudophakic rhegmatogenous retinal detachment.Case reportA 45-year-old male with a history of cataract surgeries of both eyes developed pseudophakic retinal detachment in his left eye. He received surgeries of scleral buckle and standard 3-port pars plana vitrectomy with silicon oil tamponade. With retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…However, this patient had previously undergone YAG capsulotomy. 5 Our case illustrates that silicone oil can become lodged between the IOL and an intact posterior capsule in pseudophakic patients who have previously undergone retinal detachment surgery, with migration of the oil presumably through weakness in the zonular fibers, through the capsulorhexis, and behind the IOL.…”
Section: Discussionmentioning
confidence: 78%
“…However, this patient had previously undergone YAG capsulotomy. 5 Our case illustrates that silicone oil can become lodged between the IOL and an intact posterior capsule in pseudophakic patients who have previously undergone retinal detachment surgery, with migration of the oil presumably through weakness in the zonular fibers, through the capsulorhexis, and behind the IOL.…”
Section: Discussionmentioning
confidence: 78%
“…Adhesion of foreign material to artificial intraocular lenses is a well-known phenomenon, with calcifications and silicone oil being identified as common culprits in various case studies [6][7][8][9][10][11][12][13]]. An experimental study by Kageyama and Yaguchi showed that silicone oil was most likely to interact with silicone IOLs and least likely to interact with hydrophobic acrylic lenses [9].…”
Section: Resultsmentioning
confidence: 99%
“…[ 10 ] In another case, a large silicone oil droplet adhesion on the posterior surface of IOL was removed by using a vitreous cutter. [ 11 ] Removal or replacement of the IOL was often adopted in cases where postoperative visual acuity of patients was seriously affected or where complications were caused by IOL decentration, tilt, rotation, or luxation. [ 12 ] In this case, the SS-OCT results showed a gap between the foreign body and the posterior surface of the intraocular lens, suggesting that the intraocular lens itself was normal and providing space for us to grasp the foreign body.…”
Section: Discussionmentioning
confidence: 99%